Mood, Burnout, and Dispositional Optimism in Kayak Polo Players During Their Competitive Stage - Angosto, Salvador; Salmerón-Baños, Laura; Ortín-Montero, Francisco José; Morales-Baños, Vicente; Borrego-Balsalobre, Francisco José (Frontiers in Psychology, 2021)
The main objective of performance sport is to obtain achievements at the highest level through the adequate development of the athlete. The scientific literature demonstrates the fundamental role played by the inclusion of certain psychological variables in the training plan. This study examined the psychological profile of kayak polo players through the variables of burnout, optimism and mood in the hours prior to the competition, relating these to each other and to some socio-demographic data. A sample of 86 canoeists, 60 men (69.8%) and 26 women (30.2%), with an age measurement of 24.4±9.1 years belonging to the 1st male and female kayak polo division completed the POMS-29, the LOT-R and the IBD-R. Athletes' levels of optimism were found to be significantly correlated with mood. Optimism also influenced emotional exhaustion. In addition, seniority and internationality were decisive factors in the level of optimism and mood achieved.